THE SISTEM PENJAMINAN KUALITAS MUTU OBJEK TITIP JUAL PRODUK ELEKTRONIK SECOND PADA USER PLATFORM INSTAGRAM DALAM PERSPEKTIF MABI’: STUDI PADA @CONSIGNGAMING DAN @TITIPJUAL_OKE - M. Lukman Hakim T (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
Social media is now used as a platform for a number of business endeavors, including conducting sales-related tasks. The selling of secondhand electronics is the main topic of this research. As a result, guaranteeing the quality of the products that are sold (mabi') is important for both the seller and the owner of the transaction. In addition to describing restricted time and the third Mabi's viewpoint on the sale of commodities and the quality assurance of secondary products, this study additionally describes purchasing and sales procedures. This study's research methodology uses conceptual and case methods with an empirical research methodology in which data was acquired through interviews and qualitative analysis. The study's findings indicated that, first, the practice of selling and buying secondhand products on the Instagram platforms @consigngaming and @titipjual_oke defines certain terms and conditions of sale, including the requirement that the products be original, in good condition, and worth selling; second, there is a time limit for quality assurance, with the buyer having three days to inspect the items being purchased; and third, there is a review of akad mabi’ on the sale of purchase against the guarantee of quality in purchase a secondhand item product.